Friendships in middle childhood: Links to peer and school identification, and general self‐worth. (31st October 2018) - Maunder, Rachel; Monks, Claire P.
Abstract : Children's friendships are important for well‐being and school adjustment, but few studies have examined multiple indices of friendships together in middle childhood. The current study surveyed 7‐ to 11‐year‐olds ( n  =   314) about their friendships, best friendships, friendship quality and indices of self‐worth, identification with peers, and identification with school. Peer relationships were positively related to self‐worth, but not identification with peers or school. Best friendship quality moderated the relationship between number of reciprocated friendship nominations and self‐worth. Children with a reciprocated best friend had higher friendship quality and peer identification than others. Where best friendship was reciprocated, the relationship with identification with peers was mediated via positive friendship quality. The results suggest that friendship reciprocity is particularly relevant for children's self‐worth and identification with peers. The findings are discussed in relation to the importance of fostering the development of reciprocated friendships. Statement of contribution What is already known on this subject? Friendships are related to well‐being, school relations, and how young people feel about their peers at school. Friendship quality may be important in moderating the relationship between peer relations and adjustment. What does this study add? Various aspects of friendships are studied simultaneously with younger children than much previous research. Reciprocated best friendships were better quality than partial or non‐reciprocated best friendships. Friendship reciprocity was most relevant for children's self‐worth and peer identification.